HEAVEN. Issue 49 (23rd May 2018) - Cahn, Steven M.
Abstract : The concept of Heaven raises innumerable difficulties but is so attractive that many may wish to believe in the idea regardless of any arguments against it. Even though unreasonable, it might play a positive role in some lives.